2009
DOI: 10.31729/jnma.342
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Biopsies: A Hospital Based Retrospective Study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
3
13
0
1
Order By: Relevance
“…4,10 The mixed cellularity type is the most common pattern in the current study, in agreement with other studies. 17,19 In the present study, metastatic tumors was the fourth commonest cause of lymphadenopathy constituting 12.57% cases, which is similar to the study of Shrestha AK et al 16 In agreement with others, majority of the patients (62.5%) were above the age of 45 years. 4,16 Out of 24 metastatic lesions, adenocarcinoma and squamous cell carcinomas were common comprising 37.5% and 25% respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…4,10 The mixed cellularity type is the most common pattern in the current study, in agreement with other studies. 17,19 In the present study, metastatic tumors was the fourth commonest cause of lymphadenopathy constituting 12.57% cases, which is similar to the study of Shrestha AK et al 16 In agreement with others, majority of the patients (62.5%) were above the age of 45 years. 4,16 Out of 24 metastatic lesions, adenocarcinoma and squamous cell carcinomas were common comprising 37.5% and 25% respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with other studies benign lesions were more frequent comprising 70.2% of lymph node enlargement and malignant lesions constituted 29.8%. 15,16 In contrast, a study done by Olu-Eddo AN et al 10 revealed malignancy being the predominant lesion constituting 55% of cases. The higher incidence of malignant tumors are also documented in the western series.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…1,2 Cervical lymphadenopathy is usually defined as cervical lymph nodal tissue measuring more than 1 cm in diameter. 3 This can be presented as isolated or as a part of generalized lymphadenopathy. Enlarged palpable cervical lymph node as a primary presenting sign is a very common problem in clinical practice.…”
mentioning
confidence: 99%